The system of vocational education as factor in development of human potential: regional aspect - N. V. Borovskikh; E. A. Kipervar (Омский научный вестник: Серия "Общество. История. Современность")
The article describes the features of the functioning of the system of higher and vocational education in the Omsk region. It is determined that the vocational education system directly influences the state and prospects of the labor market development, identifies the main tasks of the functioning of the education system in relation to the processes of formation and development of the personnel potential of the region. The educational potential of the Omsk region, which is characterized by a multi-level vocational education system, is considered. The problems typical for the system of secondary vocational and higher education of the Omsk Region are identified. The necessity in the implementation by the regional authorities of the long-term planning of the needs of the region for human resources and its reproduction in accordance with the identified need is considered